SISTEM PROTEKSI TEGANGAN SENTUH PADA INSTALASI LISTRIK BERBASIS EARTH LEAGAGE CIRCUIT BREAKER (ELCB) - Syarifil Anwar (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2021)
An electrical installation is a series of electrical installation equipment that connects an conductor with the electrical equipment used (consumers). The protection factor (safety) is a consideration that must be considered in designing an electrical installation so that it can be used optimally, effectively, efficiently, safely, properly and correctly while ensuring fire safety, of course in accordance with the General Requirements for Electrical Installation (PUIL) 2011. Touch voltage, which means that if a live wire is touched or held on a cable that is stripped of its insulation, then we will be electrocuted. Therefore, in the installation of electrical installations, there must be additional safety besides the Miniature Circuit Breaker (MCB). The additional safeguards are the neutral point (ground) ground and the Earth Leakege Circuit Breaker (ELCB). Electrical installations that use Earth Leakege Circuit Breaker (ELCB) safety must install a neutral point (Ground) ground as a condition for the Earth Leakege Circuit Breaker (ELCB) to work properly and correctly, meaning that if there is a touch voltage we will not be electrocuted, because the MCB and The ELCB will be disconnected (Trip) simultaneously.